Chaos and Stability in Planetary Systems - Dvorak, Rudolf; Freistetter, F.; Kurths, Jürgen (Lecture Notes in Physics, 2005)
This book is intended as an introduction to the field of planetary systems at the postgraduate level. It consists of four extensive lectures on Hamiltonian dynamics, celestial mechanics, the structure of extrasolar planetary systems and the formation of planets. As such, this volume is particularly suitable for those who need to understand the substantial connections between these different topics.